2024
DOI: 10.7150/ijms.90086
|View full text |Cite
|
Sign up to set email alerts
|

Association between hidradenitis suppurativa and atopic diseases: a multi-center, propensity-score-matched cohort study

Hui-Chin Chang,
Chen-Yu Lin,
Yu-Chen Guo
et al.

Abstract: Background: Cross-sectional evidence has suggested a high prevalence of atopic diseases in patients with hidradenitis suppurativa (HS). However, there is a lack of evidence based on longitudinal studies. This study aimed to assess the risk of different atopic diseases, including asthma, atopic dermatitis, and allergic rhinitis, in patients with HS. Methods: In this retrospective cohort study, data from the TriNetX research network were obtained. Patients with HS were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, the risk of keratopathy was especially observed in the female HS population, with the risk of greater than 1.6fold compared with non-HS female controls (HR=1.61; 95%CI=1. 24 Previous studies have reported different inflammatory eye diseases (IED) in the context of HS, among which uveitis was the most common manifestation of IED (14,15). Keratitis only accounted for 23.5% (15) and 5% ( 14) of cases in these reports.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the risk of keratopathy was especially observed in the female HS population, with the risk of greater than 1.6fold compared with non-HS female controls (HR=1.61; 95%CI=1. 24 Previous studies have reported different inflammatory eye diseases (IED) in the context of HS, among which uveitis was the most common manifestation of IED (14,15). Keratitis only accounted for 23.5% (15) and 5% ( 14) of cases in these reports.…”
Section: Discussionmentioning
confidence: 91%
“…We utilized data from the TriNetX research network, a global federated health network that aggregates electronic health records from over 100 collaborative healthcare organizations (HCOs) worldwide. TriNetX is a widely utilized platform in epidemiological and clinical dermatology research (24,25). The records within the TriNetX database undergo a comprehensive de-identification process, negating the requirement for informed consent in studies utilizing this database.…”
Section: Methodsmentioning
confidence: 99%
“…This subset retrieved the health data from 60 HCOs in the United States, and contained greater than 80 million patients' data. This subset of TriNetX was widely applied in epidemiological studies in various fields of clinical investigation [33][34][35] .…”
Section: Methodsmentioning
confidence: 99%